Pemetaan Kerawanan Longsor Berbasis Analytical Hierarchy Process di Kecamatan Hulonthalangi, Kota Gorontalo - Fahira Ramadhani Djibran; Yayu Indriati Arifin; Ninasafitri Ninasafitri (Universitas Negeri Gorontalo, 2026)
Landslide susceptibility assessment is essential for supporting geological hazard mitigation in hilly urban areas where slope morphology, lithological conditions, structural discontinuities, rainfall, and land-use dynamics interact. Hulonthalangi District, Gorontalo City, is characterized by steep hillslopes, variable lithology, structural lineaments, and settlement development along slope areas. This study aims to delineate landslide susceptibility zones using an integrated Geographic Information System and Analytical Hierarchy Process approach. Eleven conditioning factors were considered, including slope, rainfall, geology, distance from lineament, distance from stream, soil type, topographic wetness index, aspect, curvature, distance from road, and land use/land cover. The AHP weighting indicates that slope, rainfall, geology, and distance from lineament are the dominant factors controlling slope instability. The resulting landslide susceptibility map consists of five classes: very low, low, moderate, high, and very high. The high susceptibility class occupies 4.636413 km² or 45.44% of the study area, while the very high class covers 0.711134 km² or 6.97%. These zones are mainly associated with steep hillslopes, weathered and fractured lithology, proximity to structural lineaments, and areas affected by surface-water concentration. The generated susceptibility map provides a scientific basis for land-use control, slope management, infrastructure planning, and landslide mitigation in Hulonthalangi District.